THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN ACCOUNTING EDUCATION IN THE DIGITAL AGE - Atang Hermawan; Willya Achmad; Yulianah Yulianah (Research and Development Journal of Education, 2022)
This study aims to explore the role of information and communication technology (ICT) in accounting education in the digital era. This research was conducted using qualitative methods, by collecting data through in-depth interviews and observations of Accounting teachers who teach at SMK. The results of the study show that there are three ICTs that are most widely used by accounting teachers. Namely spreadsheet software such as MS Excel, learning-based computer laboratories, and word software such as MS Word while the most rare is teleconference based learning. ICT has a significant role in improving the quality of accounting education in the digital era. Information and Communication Technology (ICT) can help increase the efficiency and effectiveness of education, increase student participation and involvement, and help teachers develop learning materials that are more interesting and interactive. There are several challenges faced in implementing information technology in accounting education, such as a lack of understanding of information technology by teachers and students, as well as limited accessibility of information technology in several regions